Heidegger on the Notion of Dasein as Habited Body - Thoibisana, Akoijam (The Indo-Pacific journal of phenomenology, 2008)
Heidegger is often attacked for his failure to offer a thematic account of the body in his Being and Time (Aho, 2005). The general misunderstanding of Heidegger’s negation of body arises from the different meanings associated with the term ‘body’. Body can be understood from two perspectives: body in terms of corpse and body in terms of lived-body. Doctors study body as corpse or object because that is required in their training and education. Heidegger’s Being in his Being and Time ruled out all dichotomy of the body. The aim of this paper is to understand the Heideggerian perspective on Dasein as not a negation of bodilyness but a phenomenological understanding of Dasein body, and as such to highlight the dimension of lived-body in Heidegger’s Being and Time. The paper will re-examine how Heidegger’s philosophy of Dasein contributed to the phenomenology of lived-body in terms of his analysis of habitual body.